Investigação da diversificação e evolução cromossômica em espécies de Pimelodidae (Siluriformes): contribuição dos DNAs repetitivos e cromossomos B - Malimpensa, Geovana de Cassia (Universidade Federal de São Carlos, 2019)
Pimelodidae comprises 114 valid species, whith few of them are cytogenetically characterized, mainly, especially with respect to molecular cytogenetics. In addition, the species taxonomic delimitation is still very imprecise and problematic due to the absence of diagnoses based on phylogenetic relationships. In this context, cytogenetic analyzes (classical and molecular) and molecular (DNA barcoding, GMYC and bPTP) were carried out in four species of Pimelodidae: Bergiaria westermanni, Pimelodus fur and Pimelodus pohli from the São Francisco River basin, and Pimelodus microstoma from the Upper Paraná River basin, aiming to provide evolutionary and taxonomic subsidies for them. B. westermanni, P. microstoma and P. pohli species showed conservation concerning the diploid number (2n), heterochromatin distribution pattern, Ag-NORs/rDNA 45S sites localization, histone gene clustering, syntenia between U2 snRNA/rDNA 5S, and distribution pattern of thirteen different microsatellites. However, differentiations were found for some other cytogenetic features, such as the 2n in P. fur, the karyotype formula, number and location of 5S rDNA sites and the location of H3/H4 histones in P. microstoma, the presence of NOR bearing B chromosomes in B. westermanni, the ITS occurrence in P. pohli, the syntenia between U2 snRNA, 5S rDNA and histones in B. westermanni, and the presence of a conspicuous microsatellite (GATA)n block in P. microstoma. Such features evidence the karyotype diversification that occurred among these species along their evolutionary process and support their taxonomic delimitation. CGH data showed the sharing of B. westermanni gDNA with the gDNAs of other species, in few chromosomal regions, thus reinforcing their genetic diversification. Analysis on B. westermanni nuclei with Ag-NOR staining and FISH with 18S rDNA probe revealed the presence of zero up to five Ag-NORs and four sites of 18S rDNA sites, indicating that the Ag-NORs in the B chromosomes of this species are active regions. 18S rDNA and (GATA)n sites were identified on A and B chromosomes of B. westermanni, suggesting the probable intraspecific origin of supernumerary chromosome. This hypothesis is also supported by CGH, which has evidenced the predominance of B. westermanni genomic content in this chromosome. The molecular analyzes also supported the occurrence of four distinct species, reinforcing the taxonomic and cytogenetic data. Thus, this study present new molecular and cytogenetic data for Pimelodidae species and contributes to a better understanding of their chromosomal and molecular diversity.
Keywords: Citogenética; Delimitação de espécies; DNAs repetitivos; Diversificação cariotípica; Pimelodidae; CGH; Cytogenetics; Species delimitation; Repetitive DNAs; Karyotpe diversification; DNA barcoding; CIENCIAS BIOLOGICAS::GENETICA; CIENCIAS BIOLOGICAS::GENETICA::GENETICA ANIMAL